The Female Warrior: A Case Study Of Crowdfunding And Women’s Empowerment In Malaysia - Liu , Jia; Selamat, Nor Hafizah (2016)
The Velara Warriors is a project recently launched by two young Malaysian women to create a line of female action figures that challenges gender stereotypes in children’s entertainment. While mainstream films feature a growing number of strong female characters, toy franchises are less likely to manufacture and sell corresponding female fighting figures. The two women turned to Kickstarter, one of leading crowdfunding platforms, to raise capital from a wide network of supporters. While funding barriers faced by women have been widely addressed in literature, women entrepreneurs are more likely be funded on crowdfunding platforms like Kickstarter, demonstrating a potential to promote gender equality. Adopting a case study approach, this paper uses a gender framework suggested by Naila Kabeer as its starting point to discuss the crowdfunding phenomenon in relation to women’s empowerment. Findings suggest a positive connection between crowdfunding, women’s empowerment and entrepreneurship. The article concludes with suggestions for future research avenues.